The multifaceted ethical dilemmas of postdoctoral researchers: Toward equitable policies in international mobility - Katanov, Yosef; Shapira-Lishchinsky, Orly; Bamberger, Annette (Journal of International Students, 2026)
International postdoctoral mobility is framed as a pathway to academic development, career advancement, and global collaboration. However, for many early-career researchers, the decision to pursue a postdoctoral position abroad involves navigating conflicts between competing values: ethical dilemmas. This study identifies and examines ethical dilemmas through 40 in-depth interviews with Israeli postdoctoral researchers in the humanities and social sciences: 20 who pursued postdoctoral training abroad and 20 who remained in Israel. The findings identify recurring ethical dilemmas shaped by tensions between collective and individual values, including family stability versus professional self-fulfillment, community belonging versus professional development, and national or religious identity versus cosmopolitan academic opportunities. By conceptualizing these tensions as ethical dilemmas rather than barriers/challenges, the article offers a new lens for understanding inequality in postdoctoral mobility. The study develops a multidimensional model of ethical dilemmas and highlights the need for equitable policies that recognize family, cultural, and social contexts.